Bridging the education gap: an exploratory study of education in low-income rural and informal settlements in Namibia - Haingura, Pascalius (Graduate School of Business (GSB), 2025)
This qualitative study explores educational challenges and opportunities in low-income communities in northern Namibia and informal settlements in central Namibia. Recognising education as a key driver of national development, the research identifies significant misalignments between the educational expectations of these communities and the priorities set by the Namibian government, highlighting systemic challenges that hinder inclusive education for marginalised populations. The study is framed using the Heneveld and Craig (1995) Framework as further highlighted, tailored for sub-Saharan Africa. This framework evaluates how national education policies translate into school practices, emphasizing the importance of socio-economic and cultural factors. The research employs an exploratory qualitative design, utilizing purposive and convenience sampling to capture the experiences of teachers, education officials, parents, and community members through interviews, focus groups, policy document reviews, and field observations. Findings reveal a disconnect between government policies and community expectations, with communities dissatisfied by top-down approaches to education reform. Socio-economic challenges, local traditions, and cultural factors shape community expectations but are often overlooked in policy design and implementation. Bureaucratic inefficiencies were also cited as barriers to effective policy execution, and resource gaps, particularly inadequate teacher training and underfunded school infrastructure, further aggravated these challenges. The study advocates for community-centric education models that incorporate local traditions and practical knowledge into curricula, fostering relevance and inclusivity. Strengthening collaboration among the Ministry of Education, schools, and communities is crucial for more effective education reforms. Additionally, the research highlights the need for capacity-building initiatives to enhance teachers' cultural competence and teaching skills. Contributing to the academic discourse on education in sub-Saharan Africa, this study emphasises the need for context-specific interventions that align educational policies with socio-economic realities, cultural identities, and community aspirations. Future research is encouraged to explore the role of local traditions, bureaucratic impacts, and private school models in improving education quality and equity.